Wage Premiums as a Means to Evaluate the Labor Market for Pharmacy Technicians in the United States: 1997-2018 - David P. Zgarrick; Tatiana Bujnoch; Shane P. Desselle (MDPI AG, 2020)
Pharmacy technicians are integral members of the health care team, assisting pharmacists and other health professionals in assuring safe and effective medication use. To date, evaluation of the labor market for pharmacy technicians has been limited, and relatively little has been evaluated regarding trends in wages. The objective of this research is to use US Bureau of Labor Statistics (US BLS) data to evaluate changes in pharmacy technician wages in the United States from 1997 to 2018 relative to changes in the US consumer price index (CPI). Median hourly wages for pharmacy technicians were collected from US BLS data from 1997 to 2018. Median hourly wages were compared to expected hourly wages, with the difference, a wage premium, indicative of imbalances in the supply and demand of labor. Both positive and negative wage premiums were observed, with most positive wage premiums occurring prior to 2007 and most negative wage premiums observed after 2008. Differences in wage premiums were also observed between technicians working in various practice settings. Given the median length of employment of pharmacy technicians, it is likely that the majority of technicians working in US pharmacies have not experienced increases in their wages relative to what would be expected by changes in the CPI. This has occurred at a time when pharmacies and pharmacists are asking more of their pharmacy technicians. Researchers and pharmacy managers must continue to evaluate the pharmacy technician labor market to assure that technician wage and compensation levels attract an adequate supply of sufficiently skilled workers.